Bioconstruction: sustainable and efficient systems (Revista Cientifica Ingenio Magno, 2021)
The development of sustainable technologies is gaining more and more focus. Motivated by the demand for ecological construction techniques, a construction manual was developed using bioconstruction techniques, to democratize knowledge and revive construction techniques that do not harm the ecosystem. Among the techniques covered, the compacted earth block has as its basic principle the capacity of the earth to form a resistant aggregate from its compression. Bahareque is one of the simplest and quickest for construction: it consists of developing a plot with rigid material, where a mixture is applied, in order to fill the voids left by the plot, a light construction that does not require so much of the soil. The addition of alloys (such as sugar cane ash, rice husk and brachiaria) generates better resistance to mechanical compression and less water absorption from the blocks, encouraging the reuse of disposable materials and saving resources from the earth. Finally, in the long run, the increase in materials like this will allow the sector to significantly reduce its environmental footprint, especially considering the reduction in the amount of concrete used and the waste produced in the process.
Keywords: Alloys; Bahareque; Bioconstruction; Compressed earth block; Earth construction; Manual